The universality of power law slopes in the solar photosphere and transition region observed with HMI and IRIS - Aschwanden, Markus J.; Nhalil, Nived Vilangot (Frontiers in Astronomy and Space Sciences, 2023)
We compare the size distributions of {\sl self-organized criticality (SOC)} systems in the solar photosphere and the transition region, using magnetogram data from {\sl Helioseismic and Magnetic Imager (HMI)} and {\sl Interface Region Imaging Spectrograph (IRIS)} data. For each dataset we fit a combination of a Gaussian and a power law size distribution function, which yields information on four different physical processes: (i) photosopheric granulation convection dynamics (explaining the Gaussian random noise distribution in IRIS data); (ii) spicular plage events in the transition region (explaining the power law size distribution in IRIS data); (iii) salt-and-pepper small-scale magnetic structures (explaining the random noise distributions in HMI magnetograms); and (iv) magnetic reconnection processes in flares and nanoflares (explaining the power law size distribution in HMI data). We find a high correlation (CCC=0.97) between IRIS and HMI data. Datasets with magnetic flux balance are found to match the SOC-predicted power law slope $α_F=1.80$ for mean fluxes, which confirms the universality of SOC-inferred flux size distributions, and agrees with the results of Parnell et al.~(2009), $α_F=1.85±0.14$.